Short sleep duration and interest in sleep improvement in a multi-ethnic cohort of diverse women participating in a community-based wellness intervention: an unmet need for improvement - Sara E. Simonsen; Grant R. Sunada; Kathleen Digre; Louisa A. Stark; Valentine Mukundente; Ed Napia; Fahina Tavake-Pasi; Jeannette Villalta; Doriena Lee; France Davis; Ana Sanchez-Birkhead; B. Heather Brown; et al. (BMC, 2023)
Abstract Background Disparities in sleep duration are a modifiable contributor to increased risk for cardiometabolic disorders in communities of color. We examined the prevalence of short sleep duration and interest in improving sleep among a multi-ethnic sample of women participating in a culturally tailored wellness coaching program and discussed steps to engage communities in sleep health interventions. Methods Secondary analysis of data from a randomized trial were used. The wellness coaching trial utilized a Community-Based Participatory Research (CBPR) approach. Data were from the baseline survey and baseline wellness coaching notes. Short sleep duration was defined as < 7 h of self-reported sleep. Participants were prompted to set a goal related to healthy eating/physical activity and had the opportunity to set another goal on any topic of interest. Those who set a goal related to improving sleep or who discussed a desire to improve sleep during coaching were classified as having an interest in sleep improvement. Analyses utilized multivariable models to evaluate factors contributing to short sleep and interest in sleep improvement. We present our process of discussing results with community leaders and health workers. Results A total of 485 women of color participated in the study. Among these, 199 (41%) reported short sleep duration. In adjusted models, Blacks/African Americans and Native Hawaiians/Pacific Islanders had higher odds of reporting < 7 h of sleep than Hispanics/Latinas. Depression symptoms and self-reported stress management scores were significantly associated with short sleep duration. Interest in sleep improvement was noted in the wellness coaching notes of 52 women (10.7%); sleep was the most common focus of goals not related to healthy eating/physical activity. African Immigrants/Refugees and African Americans were less likely to report interest in sleep improvement. Community leaders and health workers reported lack of awareness of the role of sleep in health and discussed challenges to obtaining adequate sleep in their communities. Conclusion Despite the high prevalence of short sleep duration, interest in sleep improvement was generally low. This study highlights a discrepancy between need and interest, and our process of community engagement, which can inform intervention development for addressing sleep duration among diverse women.